A SEMANTIC ANALYSIS OF IMPLIED METAPHORS IN PUJANINGSIH SONG LYRICS: A CONCEPTUAL METAPHOR THEORY APPROACH - kharisma puspita sari (Undiksha Press, 2026)
Metaphor is broadly used in song lyrics to spread meanings artistically. In Javanese songs, implied metaphors are often used to express emotional and cultural meanings in elusive ways. This study aims to analyze the implied metaphors found in the lyrics of Pujaningsih and to identify the conceptual meanings represented through those metaphors. This research applied a descriptive qualitative method using conceptual metaphor theory as the analytical framework analysis. The data source of this study was the lyrics of Pujaningsih, obtained from the official YouTube channel of Wisnu Jaya. The data consisted of words, phrases, and expressions containing implied metaphors. The procedures of data analysis included identifying metaphorical expressions, classifying the implied metaphors, elaborating their conceptual meanings, and formulating conclusions. The findings reveal fifteen implied metaphors identified in the song lyrics. These metaphors revealed several conceptual mappings, such as love is a journey, woman is a precious jewel, and hope is light. The use of implied metaphors in Pujaningsih reflects emotional depth and cultural values in contemporary Javanese song lyrics. This study concludes that implied metaphors play an important role in conveying figurative meanings and enriching the aesthetic value of the song.